Profil Kebugaran Jasmani pada Siswa Tingkat Kelas Atas MIM 04 Ngemboh Kabupaten Gresik - ainul muttaqin ainul (Program Studi Pendidikan Jasmani Universitas Negeri Jakarta, 2026)
This study aimed to determine the physical fitness profile of upper-grade students at MIM 04 Ngemboh, Gresik Regency, using the Indonesian Student Physical Fitness Test (TKPN). This research employed a quantitative descriptive method involving all fourth, fifth, and sixth grade students. The instrument used was the TKPN, consisting of Body Mass Index (BMI), V Sit and Reach, Sit Up, Squat Thrust, and PACER tests. The data were analyzed using descriptive statistics in the form of percentages. The findings indicated that the students’ physical fitness level was generally in the moderate category, although some students were still classified in the low category. These findings suggest the need to improve students’ physical activity and healthy lifestyle habits to enhance their physical fitness.